Innovative Activity in Education - Surmaxon Ismoilova (Peerian Journals Publishing, 2022)
Innovations in the educational process, advanced pedagogical technologies, innovations, the use of interactive teaching methods in the teaching process, if each teacher organizes his activities based on innovations, ie lessons based on new pedagogical technologies, the student's interest increases, and the teacher achieves high efficiency. In this article, we have tried to show that the issues of educating a perfect person, ways to activate them in the educational process, and the application of new pedagogical technologies are one of the most pressing issues today
Keywords: innovation; motivation; innovative activity; interactive method